Contextual-Adaptive Integration Model of National Curriculum and Islamic Boarding School in the Development of Vocational-Based Vocational Schools - qiyadah robbaniyah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This research is motivated by the challenges of vocational education in Indonesia which are not only required to produce professionally competent graduates, but also have a strong religious character. In the context of pesantren-based vocational schools, these challenges are increasingly complex due to the need to integrate the national curriculum with pesantren values systemically. So far, studies on vocational education and Islamic boarding schools tend to be discussed separately, so there is still limited research that specifically examines the integration model of the national curriculum and Islamic boarding schools in one formal institutional system. This study aims to analyze and formulate a contextual-adaptive integration model of the national curriculum and Islamic boarding schools in the development of vocational-based vocational schools at the Mardhotullah Playen Islamic Boarding School. The research uses a qualitative approach with a case study design. Data was collected through in-depth interviews, observations, and documentation studies involving school principals and pesantren managers, then analyzed using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that curriculum integration is carried out structurally, where the national curriculum is fully adopted in accordance with regulations, while the content of pesantren is internalized through the addition of religious learning hours in the formal structure of the school. This integration is strengthened through the implementation of production-based learning and a competency-based evaluation system involving external examiners as a form of professional quality assurance. This study formulates a Contextual-Adaptive Integration Model that is rooted in the history and internal potential of the institution, is in line with national regulations, and is able to produce graduates who are vocational competent as well as religious, so as to make a theoretical and practical contribution to the development of pesantren-based vocational schools in Indonesia.